Suppressing fire hazard of poly(vinyl alcohol) based on (NH4)2[VO(HPO4)]2(C2O4)·5H2O with layered structure. Issue 45 (9th July 2021) - Zhu, Haojie; Chen, Yongming; Huang, Shuai; Wang, Yuan; Yang, Ru; Chai, Huiyu; Zhu, Fang; Kong, Qinghong; Zhang, Yunlong; Zhang, Junhao
Abstract: Two‐dimensional layered ammonium vanadium oxalate‐phosphates (AVOPh) with the structural formula of (NH4 )2 [VO(HPO4 )]2 (C2 O4 )·5H2 O are synthesized though a hydro‐thermal method, which is dispersed into poly(vinyl alcohol) (PVA) matrix to prepare PVA/AVOPh composites. The results of thermal analysis indicate that AVOPh and PVA have similar decomposition temperature from 280 to 500°C, which is critical for choosing flame retardant. The incorporation of AVOPh significantly improves the thermal stability and flame retardancy of PVA/AVOPh composites that the T5% value of PVA/2 wt% AVOPh composites is up to 215°C, and the residue of PVA/8 wt% AVOPh composites is enhanced to 16.9%, while those of pure PVA are only 178°C and 2.4%. PVA/4 wt% AVOPh composites can pass V‐0 level, and its limiting oxygen index value is up to 32.0%. Furthermore, the peak heat release rate (PHRR) and total heat release (THR) of PVA/AVOPh composites are obviously decreased, which reduced by 43.4% and 43.8% with the addition of 4 wt% AVOPh, compared with those of pure PVA. The excellent thermal stability and flame retardancy are mainly attributed to the uniform dispersion and barrier effect of 2D layered AVOPh, the release of crystal water, ammonia and phosphorus free radicals and the two‐phase flame retardant catalytic mechanism of vanadium and phosphorus. Abstract :